1989
DOI: 10.2118/15535-pa
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Pressure-Buildup Responses in Gas-Condensate Wells

Abstract: Summary Methods to analyze buildup responses in gas-condensate reservoirs producing below the dewpoint pressure are examined. Two analogs to compute formation flow capacity and average reservoir pressure are presented. These analogs are based on the steady-state theory (developed by O'Dell and Miller and later modified by Fussell) and the single-phase-flow theory (which ignores the existence of the two phases). The mechanical skin factor can be computed from the derivative response by computi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Jons and Raghavan (1986) The value of incorporating relative-permeability effects in the pseudo-pressure function is that skin due to condensate banking is already being included within the two-phase pseudo-pressure integral (Osorio et. al 2005) The authors suggested to evaluate the pseudo-pressure function based on a 2-region fluid model proposed by O'Dell andMiller (1966) andFussel (1973).…”
Section: Pseudo-pressure Functionmentioning
confidence: 99%
“…Jons and Raghavan (1986) The value of incorporating relative-permeability effects in the pseudo-pressure function is that skin due to condensate banking is already being included within the two-phase pseudo-pressure integral (Osorio et. al 2005) The authors suggested to evaluate the pseudo-pressure function based on a 2-region fluid model proposed by O'Dell andMiller (1966) andFussel (1973).…”
Section: Pseudo-pressure Functionmentioning
confidence: 99%
“…Well-test analysis is able to quantify the mobility decrease due to condensate blockage (Jones, et al, 1986), or the increase due to capillary number effects (Gringarten, et al, 2000). After the condensate bank has been formed, the radial composite model is suggested to represent zones of different fluids (Van Pollen, 1984) by considering different mobility regions as two or more circular zones surrounding the well.…”
Section: Composite Well-test Interpretation Modelsmentioning
confidence: 99%
“…The single-phase gas pseudo-pressure method does not require relative permeability information (Thompson et al, 1993;Marhaendrajana et al, 1999). Multi-phase pseudo-pressure analysis (two phase analogy) accounts for the mobility of both the condensate and gas phases (Jones et al, 1989;Ragahavan et al, 1995;Xu and Lee, 1999). This technique has been shown to provide improved estimates for mechanical skin.…”
Section: Introductionmentioning
confidence: 99%